Chemical heterogeneity of organic matter at nanoscale by AFM-based IR spectroscopy. (1st February 2020) - Abarghani, Arash; Gentzis, Thomas; Shokouhimehr, Mohammadreza; Liu, Bo; Ostadhassan, Mehdi
Highlights: AFM-IR was employed to evaluate organic matter chemical heterogeneity at nanoscale. Telalginite, degraded Tasmanites, and various types of solid bitumen were inspected. Tasmanites has lost its fluorescence due to bacterial degradation. Chemical heterogeneity has increased during the bacterial degradation process. Abstract: This study aims to differentiate between bacteria-algae interactions and thermal maturation, at the same time, shed light on the hydrocarbon generation pathways based on chemical changes at the submicron scale. For this goal, samples were taken from the lower shale member of the Bakken Formation in Willison Basin at the early and peak thermal maturity stages and analyzed with surface probes. Sample selection was based on bulk geochemical screening, organic petrology and fluorescence emission of the liptinite group macerals and solid bitumen reflectance. Submicron scale chemical heterogeneity resulting from biodegradation and different thermal maturity pathways was documented and compared using AFM-based Nano-IR spectroscopy. A significant chemical heterogeneity was noticed within unaltered telalginite and bacterially degraded Tasmanites, and also between solid bitumen particles that were adjacent to the telalginite at the same stage of maturity. Results suggest that separate pathways of maturation took place in the neighboring solid bitumen particles based on their infrared spectroscopic data. It was also found that thermal maturity progression reduced chemical heterogeneity in the organic matter particles. During bacterial degradation, Tasmanites lost its fluorescence emission while its relative chemical heterogeneity increased compared to the unaltered telalginite, a feature that has been reported at such a very fine scale of measurement. This study will ultimately improve our understanding of the processes that may result in hydrocarbon generation from organic matter.